An Analysis of Culture-Specific Items and Translation Techniques in The Yogyakarta Calendar of Events Booklet - Muhamad Safi'i (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
Translating culture-specific items (CSIs) is a complex and sensitive task requiring careful consideration of both the source and target cultures, posing significant challenges for translators. Despite the growing importance of cross-cultural communication, there is still limited research exploring how translation techniques affect the representation of local cultures. This research aims to analyze CSIs and the translation techniques used in the English translation of the Yogyakarta Calendar of Events booklet, published by the Yogyakarta Tourism Office. Adopting a descriptive qualitative approach, the research involves a comparative analysis of the Indonesian and English texts, focusing on the translation of CSIs. The analysis is conducted based on cultural categories and translation techniques as outlined by Newmark (1988). The findings reveal that the CSIs identified in the booklet fall into four categories, which include ecology (7 instances), material culture (19 instances), social culture (25 instances), and organizations, customs, activities, procedures, and concepts (37 instances). The most frequently applied translation techniques are literal translation (31 instances) and transference (28 instances), while the other techniques are used less frequently. These findings highlight the need for translators to carefully select techniques that align with the intended communicative purpose, particularly in tourism-related texts where cultural representation is crucial. Furthermore, the findings of this research shed light on how the transfer of cultural meaning is treated by translators in a working, functional context, and suggests that translation practices in tourism contexts should strike a balance between preserving cultural identity and ensuring accessibility for international audiences.